Nursing of a patient with acute exacerbation of chronic kidney disease complicated with herpes zoster (1例慢性肾脏病急性加重合并带状疱疹患者的护理体会) - LUO Liran (骆李冉); LI Qian (李倩); ZHOU Gexia (周革霞); ZHANG Caijuan (张彩娟); LIU Mengxin (刘梦鑫); JIANG Shan (王啸); (姜珊) (Journal of International Translational Medicine Limited, 2023)
This article summarized the experience of integrated traditional Chinese and western medicine treatment and nursing for a patient with acute exacerbation of chronic kidney disease complicated with herpes zoster disease. Based on syndrome differentiation, the stamp-sized sticking therapy according to syndrome type, Chinese herbal drugs collapse stains and enema of Chinese medicine decoction and other traditional Chinese medicine nursing methods. At the same time, hemodialysis and routine nursing methods were carried out in combination of Traditional Chinese Medicine. (本文总结1例慢性肾脏病急性加重合并带状疱疹疾病患者的中西医结合治疗和护理经验。首先通过辨证施护, 根据证型给予"邮票"贴敷疗法、中药塌渍及中药灌肠等中医护理方法, 同时结合西医血液透析和常规护理干预。)